2018
DOI: 10.1021/acs.jpcc.8b04822
|View full text |Cite
|
Sign up to set email alerts
|

“Deep Ultra-Strength”-Induced Band Structure Evolution in Silicon Nanowires

Abstract: Recently we experimentally demonstrated that vapor−liquid−solid (VLS) grown silicon (Si) nanowires can be stretched to above 10% elastic strain through in situ nanomechanical strategies (Zhang et al. Sci. Adv. 2016, 2 (8), e1501382). Here, based on first-principles calculation, the geometric and electric properties of <110>-oriented Si nanowires with diameter ∼1.5 nm under ultralarge strain are comparatively investigated. The anisotropic Poisson effect was observed in the silicon nanowire that the change of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…It is worth noting that if there are a large number of defects in the 2D materials’ internal region, which will obviously modulate the fracture behavior and result in multiple crack stages 55 . Furthermore, the fracture strength of the sample with edge defects remains in the same order of magnitude as the ideal strength of the defect-free sample, and the experimental measurements exceed half of the ideal value (i.e., deep ultra-strength 56 ). These effectively demonstrate that the effect of FIB on the fracture strength of monolayer Ti 3 C 2 T x nanosheets is confined to the edge area only.…”
Section: Discussionmentioning
confidence: 89%
“…It is worth noting that if there are a large number of defects in the 2D materials’ internal region, which will obviously modulate the fracture behavior and result in multiple crack stages 55 . Furthermore, the fracture strength of the sample with edge defects remains in the same order of magnitude as the ideal strength of the defect-free sample, and the experimental measurements exceed half of the ideal value (i.e., deep ultra-strength 56 ). These effectively demonstrate that the effect of FIB on the fracture strength of monolayer Ti 3 C 2 T x nanosheets is confined to the edge area only.…”
Section: Discussionmentioning
confidence: 89%
“…For example, it has been demonstrated that high-quality silicon nanowires can be stretched elastically above 10%, which is more than half of its theoretical limit (17%-20%) [92]. Accordingly, first principles calculations predicted an indirect to direct bandgap transition and a metallization transformation with ultra large strain of Si [93,94], indicating the great potential of DESE, and one may think about what DESE can do for further tuning the optical, electronic and even quantum mechanical properties of more materials.…”
Section: Deep Strain Engineeringmentioning
confidence: 99%